2019
DOI: 10.17794/rgn.2019.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Effects of Coal Dust Particle Size on Laminar Burning Velocity in a Mixture of Coal Dust and Methan

Abstract: This study investigates the effect of variations of coal dust particles size on the rate of burning of coal dust particles in a 2-liter closed chamber. Coal dust was selected from three different mines with different sizes (149µm, 125µm, 105µm, 74µm, 63µm, 53µm, 44µm, 37µm) for explosion testing in a closed chamber of 2-liters. In this analysis, the concentration of coal dust was considered constant (10000 g/m 3), all tests were carried out at a pressure of 1.5 bar and the initial temperature was 25 °C. To cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…The effect of the size of coal dust particles on their burning rate in a closed chamber was studied. From three different mines, coal dust with particle sizes of 149,125,105,74,63,53,44,37 μm was selected for explosion tests in a closed chamber with a volume of two litres (Moradi et al, 2019). All tests were carried out at a pressure of 1.5 bar and an initial temperature of 25°C.…”
Section: Analysis Of Recent Research and Publicationsmentioning
confidence: 99%
“…The effect of the size of coal dust particles on their burning rate in a closed chamber was studied. From three different mines, coal dust with particle sizes of 149,125,105,74,63,53,44,37 μm was selected for explosion tests in a closed chamber with a volume of two litres (Moradi et al, 2019). All tests were carried out at a pressure of 1.5 bar and an initial temperature of 25°C.…”
Section: Analysis Of Recent Research and Publicationsmentioning
confidence: 99%
“…The ability of dust of different coal strata to explode is evaluated using laboratory instruments, mainly, calorimeters. It is confirmed that as the particle size of coal dust decreases, its burning rate increases.Particles of coal dust with a size of 44 μm and 37 μm have a higher burning rate when compared to other sizes [2]. The analysis of laboratory experiments proved that dust with a fractional composition of 63…94 μm possesses the most explosive properties [3].…”
mentioning
confidence: 97%